PROFIL PEKERJA PEREMPUAN KORO-KORO PLAYER DI KOTA PEKANBARU - Dhani, Rahmad; ", Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This Thesis submitted in order to qualify holds a Bachelor of sociology. With the title "Women Workers Profile Koro-Koro Player in the city of Pekanbaru". The problem discussed in this essay is about women workers at the site profiles billiard koro-koro player in the city of pekanbaru. As the development of billiard in Indonesia at this time also influenced the development of the community's view of the sport of snooker player.Viewed as a billiard game with elements of "negative" which in fact is bad in opinian of the community. This is because the view of the public who saw the billiard sport activity as instead of a concentration. In its development at this time, any billiard encountered in places "negative" or place of entertainment in particular. And also billiard is always associated with gambling places, comfort women or a gathering place for young man who tend to be negative. Thus, the views of the public about this billiard is not as good place what a servant or worker who serves his guests are women. The subject of this research is four (4) respondents. The technique of determination of informants in this study by using in-depth interview techniques is a form of verbal communication or conversation with the intent of obtaining information from the object.The method used isqualitative research methods: for dekskriptifmethodin detail and depth about the problems in the meticulous. The theory used in this research is the theory of paradigm of social facts, theory, and the theory of dramaturgi human needs according to Abraham Maslow. Research results can beconcluded that the existence of a close, where the influence of the environment of the place of residence of the subject is lacking in oversight and can be categorized get freedom so that the subject can still do sidejob. And also the workplace environment is also the entertainment world or the world of the night which is a place that supports subject to find their targets.Keywords:Womenworkers, Score Girl, entertainment